2013
DOI: 10.1371/journal.pone.0076886
|View full text |Cite
|
Sign up to set email alerts
|

Dihydromyricetin Reduced Bcl-2 Expression via p53 in Human Hepatoma HepG2 Cells

Abstract: Dihydromyricetin (DHM) is a major active ingredient of flavonoids compounds. It exhibited anticancer activity and induced apoptosis in human hepatocellular carcinoma HepG2 cells according to our previous data. In this study, we investigated whether p53 is involved in DHM-triggered viability inhibition and apoptosis induction in cancer cells. MTT [3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide] assay was employed to evaluate the viability of HepG2 cells after DHM treatment. Meanwhile, p53 small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 34 publications
3
41
0
Order By: Relevance
“…We also demonstrated that at concentrations of 25 to 100 μM, DHM inhibited gastric cancer cell (AGS) proliferation and induced cell apoptosis. The antitumor effects of DHM were consistent with previous reports using liver cancer cells (Wu et al, 2013;Zhang et al, 2014). These results suggested that DHM is a potent antitumor compound that can regulate specific genes responsible for tumor cell proliferation and apoptosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also demonstrated that at concentrations of 25 to 100 μM, DHM inhibited gastric cancer cell (AGS) proliferation and induced cell apoptosis. The antitumor effects of DHM were consistent with previous reports using liver cancer cells (Wu et al, 2013;Zhang et al, 2014). These results suggested that DHM is a potent antitumor compound that can regulate specific genes responsible for tumor cell proliferation and apoptosis.…”
Section: Discussionsupporting
confidence: 90%
“…Recent reports also demonstrate potent anticancer activity of DHM (Wu et al, 2013;Zhang et al, 2014). Specifically, DHM has been found to inhibit cell proliferation in human hepatoma cells via p53-related pathways (Wu et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Dihydromyricetin (DHM) is the active component in extracts of Ampelopsis grossedentata. The principal anticancer mechanism of DHM is via the induction of p53-dependent apoptosis (73)(74)(75). A previous study demonstrated that DHM enhances chemosensitivity to nedaplatin (a platinum-containing chemotherapeutic drug) by activating the p53/B-cell lymphoma 2 (Bcl-2) signaling pathway, which resulted in mitochondrial dysfunction and induced cell death and growth inhibition in HCC cells (76).…”
Section: Sources Of Polysaccharides Targeting Growth Factors In Hccmentioning
confidence: 99%
“…It was reported that DHM could promote hepatocellular carcinoma apoptosis via the P53 activationdependent pathway [3,4]. Meanwhile it could induce Hep G2 cells autophagy involved inhibition of m-TOR [5].…”
Section: Introductionmentioning
confidence: 99%